Immunomodulation by the Commensal Microbiome During Immune-Targeted Interventions: Focus on Cancer Immune Checkpoint Inhibitor Therapy and Vaccination - Reens, Abigail L.; Cabral, Damien J.; Liang, Xue; Norton, James E.; Therien, Alex G.; Hazuda, Daria J.; Swaminathan, Gokul (Frontiers in Immunology, 2021)
Emerging evidence in clinical and preclinical studies indicates that success of immunotherapies can be impacted by the state of the microbiome. Understanding the role of the microbiome during immune-targeted interventions could help us understand heterogeneity of treatment success, predict outcomes, and develop additional strategies to improve efficacy. In this review, we discuss key studies that reveal reciprocal interactions between the microbiome, the immune system, and the outcome of immune interventions. We focus on cancer immune checkpoint inhibitor treatment and vaccination as two crucial therapeutic areas with strong potential for immunomodulation by the microbiota. By juxtaposing studies across different immune interventions, we highlight three factors prominently involved in microbial immunomodulation: short-chain fatty acids, microbe-associate molecular patterns (MAMPs), and inflammatory cytokines. Continued interrogation of these models and pathways may reveal critical mechanistic synergies between the microbiome and the immune system, resulting in novel approaches designed to influence the efficacy of immune-targeted interventions.